(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
A taxonomic study on the flora of Dohar upazila (sub-district) under Dhaka district has been conducted that results in occurrence of 204 angiosperm taxa under 165 genera and 68 families. Magnoliopsida is represented by 158 taxa distributed in 129 genera and 53 families. In contrast, Liliopsida is constituted by 46 taxa under 36 genera and 15 families. Asteraceae appears to be the largest family in Magnoliopsida consisting of 16 species, whereas Poaceae is the largest family with 16 species in Liliopsida. In Magnoliopsida, 23 families are represented by a single species, while in Liliopsida, 7 families are symbolized by a single species. Vegetation analysis shows that herbs are represented by 133 taxa, shrubs by 23 and trees by 48 taxa. Dichotomous bracketed keys to the families, genera, species and varieties are provided for easy identification of the taxa. Each taxon is supplemented by updated nomenclature, habit and representative specimen. Bangladesh J. Plant Taxon. 27(2): 293-322, 2020 (December)